CONSUMER ACCEPTANCE OF BIANG FISH (Ilisha elongata) NUGGETS WITH THE ADDITION OF YELLOW PUMPHER (Cucurbita moschata durch) - Annisa Amalia; Sumarto Sumarto; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTBiang fish (Ilisha elongata) is a fish that is rich in nutrition with protein and mineral content because it contains many fine spines with a savory and delicious taste. Biang fish can be used for various food preparations, one of which is to make nuggets which can be combined with pumpkin as a source of fiber and vitamins. The purpose of this study was to determine the best concentration of pumpkin in the processing of biang fish nuggets. The research method used was a non-factorial Completely Randomized Design (CRD) with 4 treatment levels, namely N0 (control), N1 (10% pumpkin), N2 (20% pumpkin), N3 (30% pumpkin). The parameter used in this study was the organoleptic assessment. The results showed that the N1 treatment (10% pumpkin) gave the best results with the fineness test stated that 91.25% (73 people) of the compact were brownish yellow, the texture value on the preference test stated that 93.75% (75 people) with the criteria of chewiness, and the aroma value on the preference test stated that 96.25% (78 people) with the specific smell criteria of pumpkin and sweet then the taste value stated that 92.5% (74 people) with the criteria of savory and sweet.Keywords: Ilisha elongata, Nugget, Yellow Pumpher